Pancytopenia in a 70-Year-Old African-American Male: An Unusual Presentation of a Rare Disease - Aibek E. Mirrakhimov; Alaa M. Ali; Aram Barbaryan; Nwabundo Anusim; Raya Saba; Shawn G. Kwatra; Nasir Hussain; Teresita Zdunek; Alan D. Gilman (Case Reports in Hematology)
Hairy cell leukemia is a rare lymphoid neoplasm arising from mature B-lymphocytes. Clinically, the disease presents with splenomegaly and abdominal discomfort, frequent infections, fatigue and bleeding because of related cytopenias. Bone marrow biopsy is essential for diagnosis. Below we describe a case of a 70-year-old African-American male who presented to our hematology clinic complaining of fatigue. Clinical exam and computed tomography imaging did not reveal splenic enlargement. Blood work-up revealed pancytopenia and bone marrow was diagnostic for hairy cell leukemia.The patient was started on cladribine, with gradual improvement of his symptoms and blood count abnormalities. Therefore, it is essential to keep hairy cell leukemia in the differential of pancytopenia even in the absence of a splenomegaly.